Deepwater Horizon [videorecording (DVD)] - Wahlberg, Mark, 1971-; Russell, Kurt; Malkovich, John; Rodriguez, Gina, 1984-; Hudson, Kate, 1979- (Lionsgate, 2017)
For the one hundred and twenty-six people aboard the Deepwater Horizon offshore oil rig, April 20, 2010, began like any normal day. Before day's end, the world would bear witness to one of the greatest man-made disasters in U.S. history. It reveals the brave acts of the men and women who rose to the challenge and risked everything to lead others to safety.